2019
DOI: 10.21037/jtd.2019.08.109
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of ectopic thymic tissue in patients undergoing thymectomy for myasthenia gravis

Abstract: Extended thymectomy has been considered the goal of surgery for myasthenia gravis (MG) mainly due to the existence of ectopic thymic tissue. Recently, ectopic thymic tissue has attracted increasing attention in patients with MG following thymectomy. However, the specific role of ectopic thymic tissue in patients with MG is still under debate. A systematic search of the literature was performed on PubMed and Medline according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISM) stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
8
0
1
Order By: Relevance
“…However, it is presumed that a post-thymectomy myasthenia crisis might be ascribed to the residual or ectopic thymic tissue. A review showed that the common locations of ectopic thymic tissue in mediastinal fat included anterior mediastinal fat (33.2%), pericardiophrenic angles (13.6%) and an aortopulmonary window (10.4%) [ 9 ]. Some anatomical sites (such as the pericardia-phrenic angle) might be difficult to access under the subxiphoid approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is presumed that a post-thymectomy myasthenia crisis might be ascribed to the residual or ectopic thymic tissue. A review showed that the common locations of ectopic thymic tissue in mediastinal fat included anterior mediastinal fat (33.2%), pericardiophrenic angles (13.6%) and an aortopulmonary window (10.4%) [ 9 ]. Some anatomical sites (such as the pericardia-phrenic angle) might be difficult to access under the subxiphoid approach.…”
Section: Discussionmentioning
confidence: 99%
“…As in surgical resection of thymic pathologies, the phrasing ‘the more complete the resection, the better the clinical outcome’ is also in the resection of MEPAs rather a command than an advice [ 7 , 12 ]. Of course, basic prerequisite for any surgical success are excellent preoperative imaging studies, which definitely contributed to the high success rate of parathyroidectomy in the cure of PHPT [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…An ectopic thymus can occur due to the failure of migration during embryological development [8]. Li et al [10] summarized ten studies and reported common locations of ectopic thymic tissue in mediastinal fat in patients with myasthenia gravis. Moreover, the presence of ectopic thymic tissue was investigated in different anatomical locations in 882 patients, with 509 (58%) having at least one positive location.…”
Section: Discussionmentioning
confidence: 99%